Automatic detection of welding defects. (27th December 2010) - Kountchev, Roumen K.; Rubin, Stuart H.; Todorov, Vladimir T.; Kountcheva, Roumiana A.
A new approach for the automatic detection of welding defects in digital images (X-ray or photos) is presented in this paper. Various algorithms used in the consecutive stages of the image processing – permitting the successful detection of different kinds of defects and ensuring high accuracy – are described. The method is suitable for the analysis of images of pipes, plates, etc. The experimental results obtained with the software implementation of the described algorithms prove the efficiency and reliability of the new approach. This paper points up the advantages of the presented algorithms in comparison with some well-known methods for non-destructive welding control.